Walnut Consumption May Contribute to Healthy Cardiovascular/Endothelial Function by Maintaining Membrane Integrity - Dora Jarai; Akos Koller (Life)
Cardiovascular diseases (CVDs) are the leading causes of death worldwide. A healthy diet has an important role in delaying the development of many modifiable risk factors of CVD, including abdominal obesity, high blood pressure, high plasma levels of cholesterol, and glucose. The consumption of various nuts, especially walnuts, may benefit both primary and secondary prevention due to their bioactive components. This review focuses on (1) the protective role of walnut consumption on CVD at large (2) and the potential cellular and molecular mechanisms by which they have beneficial effects on vascular endothelial function. Walnuts contain many essential ingredients (such as polyunsaturated fatty acids, phenolic compounds, and vitamin E) necessary for the healthy functioning of membranes. Since membranes are involved in nearly all processes associated with life-related function, the main underlying mechanism of walnut-improved cardiovascular function is likely based on improving membrane composition and function by providing all of the substrates necessary for membranes, such as cell, mitochondria, Golgi, nucleus, and so on. In addition to endothelial cell function, all other cells and membranes are likely to benefit from walnut consumption, suggesting that incorporating walnuts into the human diet is essential, for example, during higher physical and mental demand, such as exercise, and may mitigate the risk for the development of cardiovascular diseases and compensate for the sedentary lifestyle, especially in those of an older age.